2018
DOI: 10.1088/2399-6528/aab066
|View full text |Cite
|
Sign up to set email alerts
|

On the numerical simulation of rarefied gas flows in micro-channels

Abstract: Classical continuum methods break down for rarefied gas flows in micro-channels. Two noncontinuum hydrodynamic models are investigated here: compressible Korteweg fluid-like and Bi-Velocity (Volume Diffusion) hydrodynamic models. The pressure driven rarefied gas flow in a rectangular micro-channel in the whole range of Knudsen number is numerically considered. The Korteweg model shows improved results in comparison with standard Navier-Stokes up to Knudsen number of unity. The Bi-Velocity method is found to al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Taking into account a corrected mean-free path for flow in confined spaces, Lv et al [29] were able to improve this agreement up to a Knudsen number of 50. More recently, Christou and Dadzie achieved a match over the entire range of Knudsen number in another numerical simulation based on the Bi-velocity model [30].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Taking into account a corrected mean-free path for flow in confined spaces, Lv et al [29] were able to improve this agreement up to a Knudsen number of 50. More recently, Christou and Dadzie achieved a match over the entire range of Knudsen number in another numerical simulation based on the Bi-velocity model [30].…”
Section: Introductionmentioning
confidence: 92%
“…As stated earlier the precise nature of this coefficient is not yet known. However, in previous investigations on rarefied gas flows [30], it was assumed that…”
Section: Governing Equationsmentioning
confidence: 99%
“…Furthermore, it is found that the shear stress in Dadzie's model is exactly the same as that in Brenner's model. However, in a recent paper the parameter κ m is changed to Pr/3 [12].…”
Section: "Thermo-mechanically Consistent" Burnett Equationsmentioning
confidence: 99%
“…In the free molecular regime, the diffusive terms have a larger effect in governing the flow profiles, thereby giving a plug flow velocity profile along the channel. This plug flow profile can be noted in the numerical simulations in the works of Christou and Dadzie [43]. The new slip conditions and analytical solutions provide an alternative physical explanation for rarefied flows in micro-channels and may be adopted to interpret other non-equilibrium flow phenomenons.…”
Section: Discussionmentioning
confidence: 62%